All 3D-printed stretchable piezoelectric nanogenerator with non-protruding kirigami structure - Zhou, Xinran (2021)
With the advancement of wearable electronics, stretchable energy harvesters are attractive to reduce the need of frequent charging of wearable devices. In this work, a stretchable kirigami piezoelectric nanogenerator (PENG) based on barium titanate (BaTiO ) nanoparticles, Poly(vinylidene fluoride-co-trifluoroethylene) (P(VDF-TrFE)) matrix, and silver flakes-based electrode is fabricated in an all-3D printable process suited for additive manufacturing. The 3D printable extrusion ink is formulated for facile solvent evaporation during layer formation to enable heterogenous multilayer stacking. A well-designed modified T-joint-cut kirigami structure is realized to attain a non-protruding, high structural stretchability performance, overcoming the out-of-plane displacement of the typical kirigami structure and therefore enabling the pressing-mode of a kirigami-structured PENG. This PENG can be stretched to more than 300% strain, which shows a great potential for application in wearable electronic systems. Furthermore, a self-powered gait sensor is demonstrated using this PENG. 3